Antiemetics for Postoperative Nausea and Vomiting in Patients Undergoing Elective Arthroplasty: Scheduled or As Needed? - Antle, Ouida (Can J Hosp Pharm, 2018)
BACKGROUND: Postoperative nausea and vomiting (PONV) is one of the most commonly reported adverse experiences after surgery. PONV is a major risk factor for delayed patient mobilization and consequently increased length of hospital stay. OBJECTIVES: The primary objective was to compare the effectiveness of scheduled versus as-needed administration of antiemetic for the prevention and treatment of PONV in the first 48 h after elective hip or knee arthroplasty. The secondary objective was to determine whether PONV affected mobilization on either postoperative day 0 or postoperative day 1 in each study group. METHODS: This retrospective cohort study used chart reviews for collection of patient data. PONV and mobilization were compared for patients who received antiemetics on a scheduled or as-needed basis following elective hip or knee arthroplasty performed between January and September 2016. RESULTS: Of the 132 patients included in the study, 65 received antiemetics on an as-needed basis and 67 had scheduled antiemetic therapy. Thirty-one (46%) of the patients in the “scheduled” group received antiemetics as intended; the others missed one or more of the scheduled doses. There was no statistical difference in PONV between treatment groups with either intention-to-treat or as-treated analysis. Furthermore, there was no statistically significant difference in mobilization, on either POD 0 or POD 1, between patients who received scheduled antiemetic and those who received antiemetic on an as-needed basis. CONCLUSIONS: Scheduled use of antiemetics did not significantly affect PONV, nor did it positively influence mobilization in the postoperative period for patients undergoing elective arthroplasty. Further high-quality prospective studies are needed to confirm these results.